Sacrospinous fixation for treatment of vault prolapse and at the time of vaginal hysterectomy for marked uterovaginal prolapse - Silva-Filho, Agnaldo L.; Triginelli, Sérgio A.; Santos-Filho, Admário S.; Cândido, Eduardo B.; Traiman, Paulo; Cunha-Melo, José Renan (Wolters Kluwer, 2004)
Purpose: The purpose of this study was to evaluate the transvaginal sacrospinous ligament fixation technique in the treatment of vault prolapse and as part of the vaginal repair procedure at the same time of vaginal hysterectomy for marked uterovaginal prolapse. Materials and Methods: One hundred fifty-eight patients averaging 68.6 ± 10.6 years of age (range, 36-94 years) treated with sacrospinous ligament suspension of the vaginal vault at Hospital das Clinicas, Federal University of Minas Gerais from February 1990 to October 2002 were retrospectively studied. The study showed that 115 (72.8%) patients had marked uterovaginal prolapse and 43 (27.2%) had vault prolapse after hysterectomy. The mean follow-up period was 5.3 ± 3.9 years (range, 1.2-11 years). Results: There were 7 (4.4%) intraoperative complications of which 4 of them (2.5%) were rectal lacerations, 2 (1.3%) bladder lesions, and 1 (0.6%) excessive bleeding. The average hospitalization time was 3.1 day (range, 2-15 days). Four women (2.5%) had buttock discomfort, which subsided after 2 months, and 4 (2.5%) had perineal abscess. Follow-up examinations showed pelvic floor defects in 16 patients (11.1%); 2 (1.3%) presented total recurrence of the vault prolapse and 2 patients (1.3%) showed partial recurrence. Cystocele was evidenced in 9 patients (5.7%) and rectocele was found in 3 patients (1.9%). The postoperative vaginal wall defects were significantly higher in the patients with vault prolapse compared with those with uterovaginal prolapse (20.9% vs. 6.1%, P[r] = 0.0014). These defects did not have correlation with age (P = 1.00), parity (P = 0.154), degree of uterovaginal prolapse (P = 0.672), or type of previous hysterectomy (P = 0.657). Conclusion: Transvaginal sacrospinous fixation is efficient for the treatment of vaginal vault prolapse and can be performed together with vaginal hysterectomy in patients with marked uterovaginal prolapse.
Keywords: Transvaginal savrospinous colpopexy; Uterovaginal prolapse; Vaginal vault prolapse